The painter of his dishonour, - Calderón de la Barca, Pedro, 1600-1681 (Hispanic classics., 1991)
Alan Paterson presents Calderon's original text, from manuscript and printed sources, with a skilful verse translation into English of a remarkable play, in which Calderon develops the motif of marital honour in quite original ways. The blending of deep pathos and humour anticipates the modern theatre of the absurd, though Calderon is pushing to the limits the license gained by Lope de Vega to mingle tragedy with comedy. The play incorporates important aesthetic ideas of the Renaissance on painting and the character of the artist. It must be unique in seventeenth-century European in dramatising the painter as he works in his studio and meditates on his art. Since the play deals with the aesthetic component in human behaviour, its own aeathetic status as a verse drama had been conserved in the translation. Those with no knowledge of Spanish will find a text which is agreeable to read and to perform. The translation is close enough, however, to offer the reader of limited ability in Spanish a reliable key to the Spanish text. Spanish text with facing-page translation, introduction and commentary.